Philippine Philharmonic Orchestra, 2016, 33rd concert season 2015-2016. - Ochanine, Olivier, principal conductor; Tetsuji, Gonna, conductor; Merced-Misa, April Dawnena 1986-; Beethoven, Ludwig van 1770-1827; Beethoven, Ludwig van 1770-1827 (2016)
Philippine Philharmonic Orchestra (established May 15, 1973), as the CCP Philharmonic Orchestra and was initially intended to accompany performing artists at the Tanghalang Nicanor Abelardo (CCP Main Theater), 33rd concert season 2015-2016, Friday evening, January 22, 2016, at 8:00, Olivier Ochanine principal conductor, Honna Tetsuji conductor, April Dawnena Merced-Misa, pianist. Notes on the program by Michael Steinberg and laphil.org.